Second Church/Cockerel Church, ca. 1865 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
View of Second Church/Cockerel Church on Hanover Street. Several commercial and residential buildings line Hanover Street. Signage adorns some of the buildings, including Nixon Hazlett's business, which is located directly southwest of or next to Second Church. The church steeple is visible in the center of the photograph. Copyprint; Cockerel Church was originally erected at 1845, then rebuilt and remodelled in 1873. Image is part of the Henry P. Curtis Collection. 7 3/8 diameter (photograph is round), 8 x 10 overall Photographs